câu 1a/ x mũ 2 (x-3)-x(x mũ 2+7)+3x mũ2 +6=5 b/3x(x+6)-x(3x-3-2x+4 câu 2 a/5x(x-3)+4x(x mũ 2-3x+2) b/6x(y-3)-3y(2x+7)-6x+6

Question

câu 1a/ x mũ 2 (x-3)-x(x mũ 2+7)+3x mũ2 +6=5
b/3x(x+6)-x(3x-3-2x+4
câu 2 a/5x(x-3)+4x(x mũ 2-3x+2)
b/6x(y-3)-3y(2x+7)-6x+6

in progress 0
Madeline 4 tháng 2021-08-02T11:09:14+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-08-02T11:10:17+00:00

     Câu 1:        

          a,   $x^{2}$ ($x^{3}$) – $x^{}$ ($x^{2}$ + 7) +3$x^{2}$ + 6 =5

    <=>    $x^{3}$ – 3$x^{3}$ – $x^{3}$ – 7$x^{}$  + 3$x^{2}$  + 6 = 5

    <=>    ($x^{3}$ – $x^{3}$) + (-3$x^{2}$ + $x^{2}$) – 7$x^{}$ + 6 =5

    <=>                   0              + 0                                  – 7$x^{}$ + 6 =5

    <=>                    – 7$x^{}$ + 6 =5

    <=>                    – 7$x^{}$ =11

    <=>                        $x^{}$ = $\frac{1}{7}$ 

            

          b,   3$x^{}$ ($x^{}$ +6) – $x^{}$ ( 3$x^{}$ – 3 ) – 2$x^{}$ + 4

       = 3$x^{2}$ + 18$x^{}$ – 3$x^{2}$ + 3$x^{}$ – 2$x^{}$ +4

       = ( 3$x^{2}$  3$x^{2}$ ) + ( 18$x^{}$ + 3$x^{}$ – 2$x^{}$ ) + 4

       =           19$x^{}$ + 4

    Câu 2:

    a, 5$x^{}$ ( $x^{}$ – 3 ) + 4$x^{}$ ( $x^{2}$ – 3$x^{}$ + 2 ) 

    = 5$x^{2}$ – 15$x^{}$ + 4$x^{3}$ – 12$x^{2}$ + 2

    = ( 5$x^{2}$ – 12$x^{2}$ ) -15$x^{}$ + 4$x^{3}$ + 2

    = -7$x^{2}$ – 15$x^{}$ + 4$x^{3}$ + 2

    b, 6$x^{}$ ( $y^{}$ – 3 ) – 3$y^{}$ ( 2$x^{}$ + 7 ) – 6$x^{}$ + 6

    = 6$x^{}$$y^{}$ – 18$x^{}$ – 6$x^{}$$y^{}$ – 21$y^{}$ – 6$x^{}$ + 6

    = ( 6$x^{}$$y^{}$ – 6$x^{}$$y^{}$ ) + ( -18$x^{}$ – 6 $x^{}$ ) – 21$y^{}$ + 6

    = – 24$x^{}$ – 21$y^{}$ + 6

    CHÚC BẠN HỌC TỐT !!!!!!!!

    0
    2021-08-02T11:10:51+00:00

    Đáp án:

     

    Giải thích các bước giải:

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )